Simulating the Impact of COVID-19 on Formal Firms in Rwanda - Lees, Adrienne; Mascagni, Giulia; Santoro, Fabrizio (World Bank, Washington, DC, 2020)
Prior to COVID-19, Rwanda was booming, with economic growth exceeding ten percent in 2019. Strong growth has been accompanied by significant improvements across various human development indicators, such as poverty reduction and rising life expectancy. The pandemic has placed much of this progress in jeopardy. Exports and tourism have been hurt by border closures and disrupted trade flows, and Rwanda is already experiencing mounting balance of payment and fiscal pressures. The associated economic contraction is likely to result in significant declines in tax revenues.